QUALITY IMPROVEMENT IN ASSISTED LIVING THROUGH A NURSING EDUCATION—COMMUNITY PARTNERSHIP MODEL. (11th November 2018) - White, D; Cartwright, J; Marcus, A; Burt, M
Abstract: Enriched Clinical Learning Experiences through Partnerships (ECLEPs) in long-term residential settings is a clinical education program of the School of Nursing, Oregon Health & Science University. Throughout its history, ECLEPS faculty have partnered with nurses in different types of residential care settings to support nursing education for undergraduate students. This approach allows students to experience the complexity of residential care and the benefits of a gerontological nursing perspective. This paper reports on the most recent ECLEPs program, a two-year quality improvement (QI) initiative in which over 30 RN to BSN students participated in assisted living (AL) communities. ECLEPs students engaged with nine AL communities to produce and test educational resources and tools with the shared goal of improving communication about residents' change of condition. Working in teams, students learned about the AL community population, the supporting staff (especially unlicensed caregivers), and emergency services that respond when called. Each student team built on the work of the preceding cohort. The result is a robust set of tools to address the needed improvements at the intersection of AL, emergency services, and acute care settings. These tools are now available for use statewide. In addition, students worked with AL teams of both licensed and non-licensed staff to introduce an approach to quality improvement that is designed to simultaneously support standardized QI processes and team building. Students have supported the adoption of this approach, which continues to be used in partner ALs. Implications for replication and sustainability of the ECLEPs model are presented.